Distinct effect of partial sleep deprivation associated with gray matter changes in young and old adults - Fu, Xiao; Shi, Yanni; Xu, Hui; Xu, Dongwu (Frontiers in Aging Neuroscience, 2025)
BackgroundSleep deprivation (SD) exerts adverse effects on human brain. However, whether there were distinct effects of partial SD associated with gray matter changes in young and old adults, respectively, remains unclear.Methods42 young adults and 38 old adults were enrolled in this study. All participants underwent MRI scanning, and FreeSurfer 5.3 was used to calculate cortical thickness (CT) and cortical surface area (CSA). Paired two samples t-tests was conducted to explore CT and CSA changes. Partial SD involved restricting total sleep time to approximately three hours, compared with baseline sleep conditions.ResultsYoung adults exhibited increased biopsychological response (Sickness-Q score) following partial SD compared to the rested condition, and similar trend was observed in old adults in SD. Young adults exhibited decreased CSA of left caudal middle frontal cortex and CT of entorhinal cortex (EC), but increased CSA of left temporal pole and CT of right insula after SD. However, old adults showed increased CSA and CT in widespread brain regions, including left superior frontal cortex, left isthmus cingulate cortex and right EC. While young adults showed a significant positive correlation between percent change of CSA of left EC and the biopsychological response, old adults showed a significant negative correlation between percentage change in CT of the left isthmus cingulate cortex and biopsychological response.ConclusionDistinct effect of partial SD associated with gray matter changes were observed in young and old adults, respectively. These findings shed light on SD might affect brain structures differently in young adults and old adults.